Developing Understanding of AI-Powered Personalized Learning Concept in TVET Institutions - Muhamad Noor, Amirul Amin; Hussein, Surya Sumarni; Mustaffa, Mastura; Mohd Lokman, Anitawati; Alfiansyah, Muhammad Wisnu (Journal of Technical Education and Training, 2025)
This paper presents a conceptual model for integrating artificial intelligence (AI) into personalised learning systems within technical and vocational education and training (TVET) institutions. The proposed model utilizes AI technologies to create adaptive learning environments tailored to the unique needs and learning styles of individual students. The problem lies in the need for adaptive learning models that cater to individual learner needs while aligning with institutional goals and processes. The primary objective of this study is to develop an AI-powered personalised learning model that leverages EA to manage the complexities of implementation in TVET settings systematically. To formulate the proposed model, a qualitative research methodology was employed, involving semi-structured interviews with three practitioners from industry and academia in the field of AI and education. These interviews provided in-depth insights and perspectives on the feasibility, implementation, and potential impact of an AI-powered personalised learning model in TVET institutions. The integration of EA frameworks provides a structured approach to managing AI implementation while ensuring alignment with organisational objectives and processes. 11 factors emerged from three categories of learning theory. The significance of this research lies in its contribution to the existing body of knowledge by offering a comprehensive overview of the current state of AI and EA integration in personalised learning at TVET institutions. Overall, this conceptual model offers a comprehensive foundation for implementing AI-powered personalised learning in TVET institutions, aiming to transform traditional educational practices and better equip students with the skills they require for their future careers.